Analysis Of Water Quality Of The Babura River And Its Users By The Community With Skin Health Complaints In Medan - Marlinang Isabella Silalahi; Ivana Alice Putri; Ermi Girsang (International Journal of Health and Pharmaceutical (IJHP), 2022)
The water quality of the Babura River is increasingly worrying because of the pollution of domestic waste that occurs. The water condition of the Babura River is physically cloudy in color, looks oily and the river contains human feces. The use of polluted Babura River water can cause health complaints, including skin health problems. The purpose of this study was to determine the water quality of the Babura River, as well as the relationship between water use and skin health complaints in the community in the watershed. This research is an analytic survey using a Cross-Sectional design. There was 592 population in this study, living in the Babura River watershed in Petisah Hulu Village. The number of samples in this study was 86 households determined by the Slovin Formula where sampling was carried out by accidental sampling. Data analysis used Chi-square Test (α=95%). Sampling points were carried out at 3 locations namely Station 1, Station 2, and Station 3. The results showed that water quality had decreased in quality where the Dissolved Oxygen (DO), fecal coli, and total coliform parameters did not meet the river water quality standards according to Government Regulation of the Republic of Indonesia Number 22 of 2021 concerning the Implementation of Environmental Protection and Management. The statistical test showed that there was a relationship between the use of Babura River water and skin health complaints in the community in the watershed with a p-value of 0.000 (α<0.05). Of all respondents, 17 people experienced skin health complaints in the form of itching and dry, scaly, and peeling skin. It is recommended to the public to avoid using Babura River water directly for daily needs, to neutralize water before using it, and to related parties to try to prevent further pollution in the Babura River.